O processo de territorialização do movimento de trabalhadoras e trabalhadores por direitos na interface campo-cidade - Menezes, Hilário José (2019)
This thesis purposes to analyze the strategies adopted by the Movement of Women and Men Workers for Rights (Movimento das Trabalhadoras e dos Trabalhadores Desempregados (MTD)) for the process of territorialization, at the field/city interface, in the State of Rio Grande do Sul and the State of Bahia, through the study of the social subjects that make up the movement and their forms of organization. To this end, it analyses the action of the MTD as a social movement, which fights for rights, especially land and work, identifies the organization of the MTD based on the history of the social subjects that make up the movement and brings a debate about the territory, understood as a dialectic space, resulting from the action of the MTD. Among the various areas where the movement operates, this research has prioritized its activities in Rio Grande do Sul (municipalities of Gravataí – Portal dos Pinheiros Settlement – and Eldorado do Sul – Belo Monte Settlement –) and in Bahia (municipality of Vitória da Conquista - Zumbi dos Palmares Settlement, Carlos Lamarca Settlement and Dandara Pre-Settlement –). The methodological assumptions for conducting the research are based on the critical-dialectic method, in which life history is used to understand the object of the study. As a study strategy, the empirical research combined techniques such as field diary, descriptive recording and semi-structured interviews to produce the data, and the analysis considered the organization of social subjects directly affected by unemployment and the lack of social and labor rights, and the antagonistic and contradictory relations concerning the current economic model, which excludes and expropriates the working class. In this context, the MTD was considered as a class social movement that seeks to organize the expropriated in the struggle for democratization of access to land and work. The strategies used by the MTD, together with the workers, reveal successful actions and the conquest of territory is the concrete result of the struggle for them in the process of producing their existence.